B-cell epitopes in NTS-DBL1α of PfEMP1 recognized by human antibodies in Rosetting Plasmodium falciparum. - Letusa Albrecht; Davide Angeletti; Kirsten Moll; Karin Blomqvist; Davide Valentini; Fabio Luiz D'Alexandri; Markus Maurer; Mats Wahlgren (PLoS ONE)
Plasmodium falciparum is the most lethal of the human malaria parasites. The virulence is associated with the capacity of the infected red blood cell (iRBC) to sequester inside the deep microvasculature where it may cause obstruction of the blood-flow when binding is excessive. Rosetting, the adherence of the iRBC to uninfected erythrocytes, has been found associated with severe malaria and found to be mediated by the NTS-DBL1α-domain of Plasmodium falciparum Erythrocyte Membrane Protein 1 (PfEMP1). Here we show that the reactivity of plasma of Cameroonian children with the surface of the FCR3S1.2-iRBC correlated with the capacity to disrupt rosettes and with the antibody reactivity with a recombinant PfEMP1 (NTS-DBL1α of IT4var60) expressed by parasite FCR3S1.2. The plasma-reactivity in a microarray, consisting of 96 overlapping 15-mer long peptides covering the NTS-DBL1α domain from IT4var60 sequence, was compared with their capacity to disrupt rosettes and we identified five peptides where the reactivity were correlated. Three of the peptides were localized in subdomain-1 and 2. The other two peptide-sequences were localized in the NTS-domain and in subdomain-3. Further, principal component analysis and orthogonal partial least square analysis generated a model that supported these findings. In conclusion, human antibody reactivity with short linear-peptides of NTS-DBL1α of PfEMP1 suggests subdomains 1 and 2 to hold anti-rosetting epitopes recognized by anti-rosetting antibodies. The data suggest rosetting to be mediated by the variable areas of PfEMP1 but also to involve structurally relatively conserved areas of the molecule that may induce biologically active antibodies.